Motives of Audiences Watching Buya Yahya's Islamic Content on Al-Bahjah TV's YouTube Channel: Uses and Gratification Theory Analysis - Abdul Azis; Reza Pahlevi Ginting (SAINTIS Publishing, 2025)
This study aims to identify and understand the audience’s motives by watching Buya Yahya’s Islamic content on the Al-Bahjah TV YouTube channel using the Uses and Gratification Theory as an analytical framework. This theory explains that audiences actively choose media to fulfill specific needs. In this research, viewers' motives are categorized based on five types of needs that media can satisfy, as proposed by Katz, Gurevitch, and Haas: cognitive needs, affective needs, personal integrative needs, social integrative needs, and tension release. This study employs a descriptive qualitative method with data collection techniques including observation and in-depth interviews with three informants from diverse backgrounds to those who watches Buya Yahya’s Islamic content on the Al-Bahjah TV YouTube channel. Data were analyzed using the interactive model by Miles and Huberman, regarding data reduction, data display, and conclusion drawing. Thus, shows that the motives for watching Buya Yahya’s Islamic content are based on the five types of needs: cognitive, affective, personal integrative, social integrative, and tension release. However, the main motives are fulfilling cognitive needs, affective needs, social integrative needs, and tension release. Although the motive to fulfill personal integrative needs was present, it was not dominant nor considered a primary motive. The study also shows that Buya Yahya’s Islamic content on Al-Bahjah TV’s YouTube channel provides audiences with an in depth understanding of Islam, delivers a positive emotional impact, and offers inspiration and spiritual motivation.